Massage Therapy Applied During Static Stretching as an Approach to Reducing Ankle Injury Pain - Ronaldo Wijaya (CV. AULIANTECH, 2026)
Ankle injuries are among the most common sports-related injuries and often result in pain and limitations in joint range of motion (ROM). This study aimed to introduce and describe massage therapy applied during static stretching as a novel approach for managing pain in post-acute ankle injuries. A descriptive, practice-based research design was employed and conducted in Bengkulu Province, Indonesia. The study involved 20 clients with ankle injuries who had passed the acute phase of injury. The intervention began with light massage to observe and identify the injured area, followed by static stretching combined with massage to release muscle stiffness and myofascial trigger points, and concluded with pain assessment and ROM evaluation. The results showed that the majority of participants experienced a reduction in pain and an improvement in ROM after a single treatment session. Specifically, 70% of participants improved from mild pain to no pain with maximal ROM, 20% improved from moderate pain to no pain with maximal ROM, and 10% of participants with severe pain showed partial improvement to mild pain with moderate ROM. These findings indicate that massage therapy applied during static stretching is effective in reducing pain and improving ROM in post-acute ankle injuries, particularly in cases with mild to moderate pain. This method is recommended for application only after the acute phase of injury has resolved and in the absence of active inflammation.